2003
DOI: 10.3201/eid0912.020520
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Infectious Diseases in Mongolia

Abstract: Since 1990, Mongolia’s health system has been in transition. Impressive gains have been accomplished through a national immunization program, which was instituted in 1991. Nevertheless, the country continues to confront four major chronic infections: hepatitis B and C, brucellosis, tuberculosis, and sexually transmitted diseases (STDs). As of 2001, only two cases of HIV infections had been detected in Mongolia, but concern grows that the rate will increase along with the rising rates of STDs and increase in to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 19 publications
2
67
0
3
Order By: Relevance
“…The result from our study was higher than the 0.1% to 10.1% reported among high-risk people in other countries, 10,15-21 which is not surprising as Mongolia is ranked second in the world for brucellosis incidence. 5 We also estimated a much higher incidence compared with that reported from notification data, 22 despite the fact that we have taken a conservative assumption that 20% of seropositive cases are clinical cases.…”
mentioning
confidence: 64%
“…The result from our study was higher than the 0.1% to 10.1% reported among high-risk people in other countries, 10,15-21 which is not surprising as Mongolia is ranked second in the world for brucellosis incidence. 5 We also estimated a much higher incidence compared with that reported from notification data, 22 despite the fact that we have taken a conservative assumption that 20% of seropositive cases are clinical cases.…”
mentioning
confidence: 64%
“…A national seroepidemiologic survey in 2002 showed that 10-12% of the adult population and 5% of children younger than 5 years were HBsAg positive. Taiwan also has a high rate of HBsAg seroprevalence (10-14%) among its adult population, whereas prevalence rates in the Philippines are 2-16.5%, Vietnam and Thailand 14%, and Southeast Asia, Japan, Korea, and India at a more modest 2-5% [2,3,6,7,9,11,13]. In many developing countries, HBsAg seroprevalence also differs between urban and rural areas.…”
Section: Prevalence Of Chb Among Asian Women Of Childbearing Agementioning
confidence: 99%
“…The rate of HBV infection is estimated to be 36-57% and HBsAg prevalence ranges from 3.8 to 16.8% in Mainland China, with higher rates observed in rural areas [1]. The seroprevalence of HBsAg among adults in other Asian countries has remained similar over the past two decades, ranging from 2 to 20% [2][3][4][5][6][7][8][9][10][11][12][13]. CHB runs an insidious and often progressive course and, when left untreated, can lead to cirrhosis, decompensated liver disease, and hepatocellular carcinoma (HCC) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Although infected animals are not seen as infectious agents to be systematically eradicated, the Mongolian government has sought to impose this understanding since the first half of the twentieth century, a goal that has been reinforced since the country's accession to the World Organization of Animal Health. Many parasitic, bacterial, and viral animal diseases were under control during the Communist period (Ebright, Altantsetseg, and Oyungerel 2003;Odontsetseg, Mweene, and Kida 2005;Roth 2007;Zinsstag et al 2007). According to an NGO veterinarian, at that time, 'veterinarians were very well trained in Moscow and herders received an exemplary and complete animal health service', and some herders remember that era 'with nostalgia' (Ulaanbaatar, winter 2014).…”
Section: Foot-and-mouth Disease: Veterinarians Enter the Environmentmentioning
confidence: 99%